Diversity in under-researched countries: new empirical fields challenging old theories?. Issue 7 (9th May 2019) - Klarsfeld, Alain; Knappert, Lena; Kornau, Angela; Ngunjiri, Faith Wambura; Sieben, Barbara
Abstract : Purpose: The purpose of this paper is to further restore diversity and equality to its national contexts by presenting new and so far less visible perspectives from under-researched countries. Design/methodology/approach: This special issue consists of five articles representing four countries and one country-cluster: Bangladesh, Bosnia and Herzegovina, Ethiopia, Korea and the English-speaking Caribbean. Three of the contributions are focused on gender diversity, while the remaining two are more general descriptions of diversity challenges and policies in the respective countries (namely, Bosnia and Herzegovina, and the English-speaking Caribbean). Findings: In addition to providing an overview of this issue's articles, this paper highlights developments and current themes in country-specific equality and diversity scholarship. In particular, drawing on the special issue's five papers, and building on the main threads that weave the special issue together, the authors show both the relevance of (some) western theories while also pointing to the need for reformulation of others. Research limitations/implications: The authors conclude with a call to further explore under-researched contexts and especially to develop locally relevant, culture-sensitive theoretical frameworks. Originality/value: How do smaller and less developed countries experience equality and diversity concepts? How are their approaches different from those experienced in already researched countries, or, on the contrary, what commonalities can be found found among them? How do theoretical frameworks originated in the West apply (or not) in these less studied countries? Are new, locally grounded frameworks needed to better capture the developments at play? Such are questions addressed by the contributions to this special issue.